A Case of Metastatic Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome-Associated Renal Cell Carcinoma Treated with a Sequence of Axitinib and Nivolumab Following Cytoreductive Nephrectomy (Journal of Kidney Cancer, 2020)
Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC) associated renal cell carcinoma (RCC) is an aggressive form of type 2 papillary RCC caused by deficiency of the fumarate hydratase gene. For patients with metastatic disease, no standard treatment has been established with dismal prognosis. We report a case of metastatic HLRCC-associated RCC in a 65-year-old Japanese male whose clinical features mimicked advanced renal pelvic cancer. A durable response was achieved with a sequence of axitinib and nivolumab after cytoreductive and diagnostic nephrectomy. Their potential therapeutic roles in the management of metastatic HLRCC-associated RCC have been discussed based on its molecular and biological backgrounds.